Factors associated with falls in hemodialysis patients: a case-control study - Ignacio Perez-Gurbindo; Ana María Álvarez-Méndez; Rafael Pérez-García; Patricia Arribas-Cobo; María Teresa Angulo Carrere (Universidade de São Paulo, 2021)
Objective: to identify possible associations between a higher probability of falls among hemodialysis patients and laboratory values, comorbidities, pharmacological treatment, hemodynamic changes, dialysis results and stabilometric alterations. Method: this was a retrospective case-control study with hemodialysis patients. Patients in a hemodialysis unit who had suffered one or more falls were included in the case group. Patients from the same unit who had not suffered falls were the controls. Data were gathered from the patients' clinical history and also from the results of a balance test conducted six months before the study. Results: thirty-one patients were included (10 cases and 21 controls). Intradialytic body weight change was significantly greater among cases (p <0.05). Patients in the case group also presented greater lateral instability after dialysis (p <0.05). Other factors such as high blood pressure, antihypertensives, beta-blockers, and lower heart rates were also associated with falls. Conclusion: a greater intradialytic weight change was associated with an increase in risk of falls. Nursing staff can control these factors to prevent the incidence of falls in dialysis patients.